2013
DOI: 10.1073/pnas.1320771110
|View full text |Cite
|
Sign up to set email alerts
|

RH5–Basigin interaction plays a major role in the host tropism of Plasmodium falciparum

Abstract: Plasmodium falciparum, the cause of almost all human malaria mortality, is a member of the Laverania subgenus which infects African great apes. Interestingly, Laverania parasites exhibit strict host specificity in their natural environment: P. reichenowi, P. billcollinsi, and P. gaboni infect only chimpanzees; P. praefalciparum, P. blacklocki, and P. adleri are restricted to gorillas, and P. falciparum is pandemic in humans. The molecular mechanism(s) responsible for these host restrictions are not understood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 41 publications
6
137
0
1
Order By: Relevance
“…This definitely was a great advancement, because previously such potent strain-transcending inhibition against multiple P. falciparum strains could not be demonstrated with leading essential blood-stage vaccine candidates (AMA-1, MSP-1). PfRH5 was also shown to be a major determinant of host cell tropism, which was first reported for P. falciparum invasion of Aotus nancymaae erythrocytes (5) and later for other species (8,26). Thus, PfRH5 emerged as an essential erythrocyte-binding protein that played a crucial role in erythrocyte invasion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This definitely was a great advancement, because previously such potent strain-transcending inhibition against multiple P. falciparum strains could not be demonstrated with leading essential blood-stage vaccine candidates (AMA-1, MSP-1). PfRH5 was also shown to be a major determinant of host cell tropism, which was first reported for P. falciparum invasion of Aotus nancymaae erythrocytes (5) and later for other species (8,26). Thus, PfRH5 emerged as an essential erythrocyte-binding protein that played a crucial role in erythrocyte invasion.…”
Section: Discussionmentioning
confidence: 94%
“…The quest to develop successful blood-stage malaria vaccines that efficiently block this process have focused on essential parasite proteins like merozoite surface protein 1 (MSP-1) and apical membrane antigen 1 (AMA-1); however, these are highly polymorphic, unable to elicit strain-transcending neutralizing antibodies, and have thus failed in field trials (4). Among the large repertoire of invasionrelated proteins, the family of P. falciparum reticulocyte bindinglike homologous (PfRH) proteins have emerged as key determinants of different invasion pathways (2,3), of which PfRH5 is the only essential conserved parasite ligand (5)(6)(7)(8) that elicits potent strain-transcending neutralizing antibodies (9)(10)(11)(12). It is localized in the rhoptry and secreted to the merozoite surface during erythrocyte invasion (6).…”
mentioning
confidence: 99%
“…It has also been reported that PfRh5 binds chimpanzee BSG with a significantly lower affinity than human BSG, and that it does not bind gorilla BSG (4). These observations suggest that the PfRh5-BSG interaction plays important roles not only in erythrocyte invasion by P. falciparum but also in the host species preferences of P. falciparum.…”
Section: Introductionmentioning
confidence: 83%
“…RH5 is also essential (16,21) and forms a critical nonredundant interaction with its receptor basigin (CD147) on the RBC surface (22). Somewhat surprisingly, RH5 appears to be under relatively low-level immune pressure following natural infection (12,(23)(24)(25)(26), with functional constraints also linked to basigin binding and host RBC tropism (21,27,28) -both of these factors potentially explain its relatively high degree of sequence conservation. Recently, the N-terminal region of RH5 (RH5Nt) has been shown to bind the essential glycosylphosphatidylinositol-anchored (GPI-anchored) merozoite protein P113, providing a mechanism for anchoring RH5 to the merozoite surface (29).…”
Section: Introductionmentioning
confidence: 99%